2016
DOI: 10.1175/jcli-d-15-0545.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Modulations of Oceanic Imprints on the Wintertime Atmospheric Boundary Layer under the Changing Dynamical Regimes of the Kuroshio Extension

Abstract: The Kuroshio Extension (KE) fluctuates between its different dynamic regimes on (quasi) decadal time scales. In its stable (unstable) regime, the KE jet is strengthened (weakened) and less (more) meandering. The present study investigates wintertime mesoscale atmospheric structures modulated under the changing KE regimes, as revealed in high-resolution satellite data and data from a particular atmospheric reanalysis (ERAInterim). In the unstable KE regime, a positive anomaly in sea surface temperature (SST) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 72 publications
6
19
0
Order By: Relevance
“…Compared to the JRA-55C, representation of surface wind convergence is slightly improved in the main JRA-55 thanks to assimilated satellite observations (not shown), although the signature is still much weaker than in the JRA-55CHS. Furthermore, the features in the JRA-55CHS are consistent with ERA-Interim for 2002−2012 (Masunaga et al 2016) and the Climate Forecast System Reanalysis (CFSR; Saha et al 2010; not shown), and therefore the JRA-55CHS is likely to be more realistic than JRA-55C. These results add another suggestion for the importance of high-resolution SST for an atmospheric reanalysis.…”
Section: Impacts Of Regime Changes Of the Kuroshio Extensionsupporting
confidence: 60%
See 2 more Smart Citations
“…Compared to the JRA-55C, representation of surface wind convergence is slightly improved in the main JRA-55 thanks to assimilated satellite observations (not shown), although the signature is still much weaker than in the JRA-55CHS. Furthermore, the features in the JRA-55CHS are consistent with ERA-Interim for 2002−2012 (Masunaga et al 2016) and the Climate Forecast System Reanalysis (CFSR; Saha et al 2010; not shown), and therefore the JRA-55CHS is likely to be more realistic than JRA-55C. These results add another suggestion for the importance of high-resolution SST for an atmospheric reanalysis.…”
Section: Impacts Of Regime Changes Of the Kuroshio Extensionsupporting
confidence: 60%
“…6h) than in the unstable regime (Fig. 6g), which can be interpreted as results of enhanced vertical mixing of momentum and/or adjustment of sea-level pressure through hydrostatic balance (Masunaga et al 2016). Accordingly, a precipitation band is confined meridionally into the climatological KE in its stable regime (Fig.…”
Section: Impacts Of Regime Changes Of the Kuroshio Extensionmentioning
confidence: 89%
See 1 more Smart Citation
“…The SST data compiled in the ERA‐Interim reanalysis data set were also used where National Centers for Environmental Prediction (NCEP) real‐time global SST (NCEP RTG) and Operational SST and sea‐ice analysis had been used before and after January 2009, respectively. The horizontal resolution of the SST data used for the ERA‐Interim reanalysis since 2002 is high enough to resolve mesoscale impacts of the fine‐scale SST distribution associated with the Kuroshio and its extension on the MBL [ Masunaga et al ., , ].…”
Section: Datamentioning
confidence: 99%
“…Featured by its strong SST gradient, the meridional shift of OE front could generate enhanced SST anomaly (Pak et al, ) and affect the overlaying atmospheric circulation and storm activity (Frankignoul et al, ; Smirnov et al, ). Especially in the low frequency (interannual to decadal time scales), SST anomalies in the OE front are considered as the driven force of atmosphere variability (Masunaga et al, ; Revelard et al, ; Taguchi et al, ) and the North Pacific decadal climate change (Kwon et al, ; Nakamura et al, ; Nakamura & Yamagata, ; Qiu et al, ). The meridional shift of OE front has been in the past attributed to the basin‐scale wind forcing (Kwon & Deser, ; Nonaka et al, ; Schneider et al, ; Seager et al, ) via the oceanic Rossby wave adjustment that modulates the latitude and strength of the OE front (Kwon et al, ; Nonaka et al, ).…”
Section: Introductionmentioning
confidence: 99%